Systematics and evolutionary significance of the small Abrocomidae from the early Miocene of southern South America - Verzi, Diego Hector (2017)
Octodontoidea is the most species-rich clade among hystricomorph rodents, and has a fossil record going back to at least the late Oligocene. Affinities of fossils previous to the late Miocene differentiation of the extant families Abrocomidae, Echimyidae and Octodontidae are controversial, essentially because these fossils may share few apomorphies with modern species. In fact, pre-late Miocene representatives of Abrocomidae had not been recognised until very recently. Here we revise the early Miocene genus Acarechimys, originally assigned to Echimyidae, and alternatively to stem Octodontoidea or to Octodontidae. A systematic and parsimony-based phylogenetic analysis of the species traditionally included in Acarechimys showed that this genus is part of stem Abrocomidae. These results are primarily supported by morphology of the mandible and lower molars. Acarechimys is here restricted to three species, A. minutus, A. pulchellus and Acarechimys pascuali sp. nov., while another species, A. constans, is here transferred to a new abrocomid genus. The remaining species were nested within Octodontidae. According to these results, Abrocomidae might have been as diverse as its sister clade Octodontidae-Echimyidae during the late Oligocene–early Miocene. Extinction of this diversity would have resulted in marked loss of evolutionary history, with extant abrocomids being currently restricted to late-diverged euhypsodont representatives.